Cover Feature: Magnetic Relaxation and Modification of Thiol Groups on Co‐Mg Ferrite Nanoparticles for Theranostics (ChemNanoMat 10/2022). Issue 10 (20th September 2022) - Katayanagi, Hikaru; Sakai, Naoki; Hamada, Sota; Usui, Akihito; Aoki, Kota; Kodama, Keita; Nashimoto, Kentaro; Hosokai, Yoshiyuki; Ichiyanagi, Yuko
Abstract : Magnetic nanoparticles (MNPs) have been actively researched for biomedical applications. This work reports the magnetic and thermal properties of various types of MNPs and confirms a significant hyperthermia effect of Mn‐Zn ferrite nanoparticles in human breast cancer cells. Doping with Co ions with larger anisotropy is a possible approach to obtain higher magnetization. However, Co‐ferrite particles exhibit hysteresis in their magnetization curves, hindering the maintenance of the superparamagnetic behavior. In contrast, Mg‐ferrite micro‐order clusters have remarkable heat generation properties for hyperthermia treatment in external magnetic fields. Thus, new properties can be expected from the synergistic effect of Co and Mg ions. Co1‐ x Mg x Fe2 O4 ( x = 0.0, 0.2, 0.4, 0.6, 0.8, 1.0) nanoparticles embedded in amorphous SiO2 with particle sizes of approximately 4.5 nm were prepared using an original wet chemical method. Spin‐echo magnetic resonance imaging measurements were performed for Co1‐ x Mg x Fe2 O4 nanoparticles using a 0.3‐T MRI system. The particles exhibited a significant T 2 shortening effect compared with that of agarose, depending on the composition. All particles exhibited effective relaxivity, R2, and a significant contrast was observed in the phantom image. More information can be found in the Research Article by Yuko Ichiyanagi et al.